Adult learners’ perception on teaching styles / Anisa Adnin Abd Rashid - Abd Rashid, Anisa Adnin (2010)
This study investigated adult students’ perceptions on the lecturers’ teaching style and the extent to which aspect(s) received the highest mean score from all seven domains featured in PALS. The study also examined the relationship between students’ selected demographic variables, namely, their gender and age, and perceptions on lecturers’ teaching styles. Respondents were thirty nine off-campus undergraduate program students of the Faculty of Education, Universiti Teknologi Mara Terengganu, Dungun Campus. Information on students’ perceptions of their lecturers’ teaching style was gathered through Adapted PALS (APALS), a questionnaire that was distributed randomly to the targeted population. Data analysis indicated that lecturers were more teacher-centered in everyday teaching. It resulted that Participation in the Learning Process was the aspect obtaining the highest mean score compared to other domains. There was no statistically significant relationship between the perceived teaching styles of lecturers’ with neither students’ gender nor age. The result indicated that students from age twenty one to thirty tend to rate their lecturers as teacher-centered. The study offers additional reflection to the lecturers in providing education to adult students.